Ethics, law and society. - Gunning, Jennifer; Holm, Søren, 1963-; Kenway, Ian (Ashgate, 2009)
This volume brings together selected papers commissioned and published by the Cardiff Centre for Ethics, Law & Society and includes contributions from international experts on topics including agriculture, ethics and bioethics.